A characterization of clouds over the Great Barrier Reef and the role of local forcing. (2nd May 2022) - Zhao, Wenhui; Huang, Yi; Siems, Steven; Manton, Michael
Abstract: A characterization of cloud properties associated with precipitation in the region around the Great Barrier Reef (GBR) is constructed using decade‐long (2007–2017) satellite observations from Moderate Resolution Imaging Spectroradiometer (MODIS) and Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO) combined with CloudSat. The spatial and vertical distributions of low‐level cloud properties over the region are also investigated and discussed. In general, different cloud types are observed over different regions and vary by season: high clouds are dominant over the low latitudes in summer, altocumulus are mainly observed over northeast Queensland and low‐level clouds are dominant over the ocean and coast during the winter months at higher latitudes under a trade wind regime. A strong latitudinal dependence of total precipitation across the Greater GBR region is identified with a significant orographic enhancement near Cairns in the wet tropics. MODIS and CloudSat‐CALIPSO cloud observations show good agreement on significant differences in low‐level cloud microphysical properties between the land and the ocean. The largest land–ocean differences in warm cloud microphysical properties are found over the mid‐latitudes near 18°S, which is strongly associated with orographic forcing, with these enhancements extending further east to the coral reef area. However, the frequency of warm cloud is not enhanced upwind of the mountains in the wet tropics. In addition, no significant differences in warm cloud properties between the actual GBR and the open ocean are identified. These results suggest that low‐level clouds over the GBR do not show any significant response to the reef‐related microphysical perturbations. Abstract : Different cloud types are observed over different areas of the Great Barrier Reef (GBR) region and vary by season. Independent satellite observations show good agreement on significant warm cloud properties orography enhancement near Cairns in the wet tropics, with these enhancements extending further east to the coral reef area. There is no significant response of low‐level clouds to the reef‐related microphysical perturbations identified over the GBR region.